(untitled) (Archaeologia Adriatica, 2008)
The two main periods of the career of the academician Nenad Cambi are related to two prominent institutions. In the Archaeological Museum in Split, he was curator of the classical collection, and for a time director, while at the Faculty of Arts in Zadar, recently declared the University of Zadar, he became a full professor, and then professor emeritus of Classical and Early Christian Studies in the Department of Archaeology.